Spatial Temporal of School Dropout Hot Spot : A Case Study of Sarawak District Education - Danggat, Chabo; Tarmiji, Masron; Norita, Jubit; Nur Faziera, Yaakub (UPSI Press, 2022)
The Ministry of Education Malaysia (MOE) has achieved remarkable successes midway between the implementation of education policy for all through the Malaysia Education Development Plan 2013-2025. However, dropout, especially at the secondary school level, relics stagnant as an educational issue in the country. Therefore, this study aims to identify the changes in the spatial pattern of dropout among secondary school students in Sarawak for a study period of six years starting from 2013 to 2018. The spatial methods applied in this study to identify dropout hotspot areas for secondary school students are Getis-OrdGi* and polygon grid (fishnet). The analysis conducted from 2013 to 2018 revealed that the hotspot areas for secondary school dropouts were intense within the District Education Office of Kuching, Sibu, and Bintulu.In conclusion, the identification of student dropout hot spots based on time and space is very important so that intervention programmes to manage dropout can be implemented based on location.The findings of this study can help stakeholders of secondary school education in Sarawak to emphasis more on the hotspot areas that have been identified.